Priapism in the Newborn: Shall We Intervene? - Laamiri, Rachida; Kechiche, Nahla; Maatouk, Mezri; Haggui, Besma; Mnari, Walid; Mekki, Mongi; Nouri, Abdellatif (Journal of Neonatal Surgery, 2016)
Idiopathic neonatal priapism is rarely published. We report the case of a newborn presenting with priapism on the first day of life and reviewed the published data on the management and the follow up of this condition.